Comparison of the efficacy of aerosolized inhalation of different doses of recombinant human interferon alpha1b combined with budesonide in the treatment of asthmatic bronchitis in children - Huang, Long; Lei, Hongyu; Zhang, Qin; Chen, Yong; Li, Kexing; Li, Delian (Frontiers in Pediatrics, 2025)
BackgroundAsthmatic Bronchitis (AB) is the most common type of bronchitis in children, severely affecting their quality of life and growth. This study aimed to investigate the efficacy and safety of aerosol inhalation of different doses of Recombinant Human Interferon alpha1b (IFNα1b) combined with budesonide in treating childhood AB.MethodsThis was a retrospective cohort study. A total of 150 children with AB treated in our hospital from December 2022 to January 2025 were retrospectively screened. They were divided into three groups based on treatment protocols: control group (budesonide alone), low-dose group (2.0 µg/kg IFNα1b+ budesonide), and high-dose group (3.0 µg/kg IFNα1b+ budesonide). The three groups were matched 1:1:1 by gender, age, disease duration, and allergy history. The primary outcomes were the remission time of cough, wheezing, and pulmonary rales. The secondary outcomes included improvements in pulmonary function indices, changes in immunoglobulin levels, and adverse events.ResultsAfter treatment, the remission times of cough, wheezing, and pulmonary rales in the high-dose group were significantly shorter than those in the low-dose and control groups, and the low-dose group was significantly shorter than the control group (all p < 0.05). The high-dose group showed significantly better improvements in pulmonary function and immunoglobulin levels than the control and low-dose groups, and the low-dose group also outperformed the control group (all p < 0.05). There were no significant differences in adverse events among the three groups (p > 0.05).ConclusionHigh-dose (3.0 µg/kg) IFNα1b combined with budesonide has certain advantages in improving cough, wheezing, pulmonary rales, pulmonary function, and immune status in children with AB, providing new clinical references for treatment.